The Role of Job Motivation in Faculty Members’ Participation in Curriculum Development - Zahra Zeinaddiny Meymand; Parvaneh Sharifi (Strides in Development of Medical Education, 2019)
Background Higher education researchers always need to analyze the factors that influence the faculty members’ participation in curriculum development. Objectives The purpose of this study was to investigate the role of faculty members’ job motivation in their participation in academic curriculum development. Methods This was a cross-sectional descriptive-analytical study. The statistical population of the study consisted of all faculty members of Islamic Azad University, Kerman branch (213 faculty members), of whom 137 subjects were selected by simple random sampling. Data were collected using Hackman and Oldham job motivation scale and academic planning questionnaire by Zeinaddiny-Meymand. Data were analyzed using descriptive and inferential statistics, including Pearson’s correlation coefficient and regression analysis using SPSS software. Results Job motivation and its components played an important role in the role of faculty members for curriculum development as “active planning”. Task significance (r = 0.520) followed by skill variety (r = 0.490), task identity (r = 0.330), job feedback (r = 0.280), and autonomy (r = 0.164) were effective, respectively. Conclusions Considering the importance of faculty members’ job motivation for their active role in curriculum development, it is necessary to provide a good motivational system in higher education and universities to promote their attitudes toward understanding the significance and identity of their jobs. In addition to that, a suitable motivational system is essential to promote and diversify multiple specialized professional skills and to provide appropriate job feedback as well as securing the autonomy of faculty members.